Using the Active Faults of Eurasia Database for solving tectonic problems - D. M. Bachmanov; E. A. Zelenin; A. I. Kozhurin; V. G. Trifonov (Геодинамика и тектонофизика)
The article describes principles, methods and tasks of tectonic studies using computer processing of the Active Faults of Eurasia Database. This new database contains more than 30000 objects that are geographically linked, equipped with attributes of the kinematic type, estimated movement rates and activity confidence ranks. As an exam‐ ple, we consider processing of the data on several tectonic regions of the Alpine‐Himalayan mobile belt and construction of rose‐diagrams of faults for a comparative analysis of their Late Cenozoic kinematics. The processed data set also covered the Caucasus‐Anatolian region and the entire central part of the mobile belt, and fields of shortening/lengthening and shearing were mapped to assess the patterns of these processes in different areas and to determine the characteristics of the tectonic flow of the upper crust material. Prospects are discussed for the database processing with the use of all the available attributive information for structural‐kinematic and geodynamic analysis, including processing of the database in combination with independent remote and geophysical data.